The Intertwined Evolution and Development of Sutures and Cranial Morphology - White, Heather E.; Goswami, Anjali; Tucker, Abigail S. (Frontiers in Cell and Developmental Biology, 2021)
Phenotypic variation across mammals is vast and reflects their ecological diversification into a remarkable range of habitats on every continent and in every ocean. The skull performs many functions to enable each species to thrive within its unique ecological niche, from prey acquisition, feeding, sensory capture to brain protection. Diversity of skull function is reflected by its complex and highly variable morphology. Cranial morphology can be quantified using geometric morphometric techniques to offer invaluable insights into evolutionary patterns, ecomorphology, development, taxonomy, and phylogenetics. Therefore, the skull is one of the best suited skeletal elements for developmental and evolutionary analyses. In contrast, less attention is dedicated to the fibrous sutural joints separating the cranial bones. Throughout postnatal craniofacial development, sutures function as sites of bone growth, accommodating expansion of a growing brain. As growth frontiers, cranial sutures are actively responsible for the size and shape of the cranial bones, with overall skull shape being altered by changes to both the level and time period of activity of a given cranial suture. Beyond this crucial role, sutures also function postnatally to provide locomotive shock absorption, allow joint mobility during feeding, and, in later postnatal stages, suture fusion acts to protect the developed brain. In keeping with this, pathological premature closure of sutures postnatally causes profound misshaping of the skull (craniosynostosis). All these sutural functions have a clear impact on overall cranial function, development and morphology, and highlight the importance that patterns of suture development have in shaping the diversity of cranial morphology across taxa. Here we focus on the mammalian cranial system and review the intrinsic relationship between suture development and morphology and cranial shape from an evolutionary developmental biology perspective, with a view to understanding the influence of sutures on evolutionary diversity. Future work integrating suture development into a comparative evolutionary framework will be instrumental to understanding how developmental mechanisms shaping sutures ultimately influence evolutionary diversity.